(untitled) (Philological Studies, 2019)
The influence of factors of speech frequency, phonetic similarity (cognates) and the presence of a motivating semantic connection (“internal form of a word”) on the word activation when moving from the native language to the unit of the second one and vice versa is considered in the article. It is shown that the lexicon in the native language (Russian) is organized semantically and the units store the speech frequency. A foreign language lexicon “builds on” it, while the search of Czech units is carried out according to a formal (phonetic) principle. The presence of a real etymological link between the closely related units of bilingual lexicon is ignored by the students, instead there is a tendency to false etymologization.